The Impact of Implementing the Carousel Brainstorming Strategy to Improve Students' Critical Reading Comprehension in Revolution 5.0 - Yusrizal, Yusrizal; Susanto, Ferri; Kurniawan, Ildi (UNIB Press, 2025)
This study investigated the effect of the Carousel Brainstorming strategy on students' critical reading comprehension. A mixed-methods approach was used, combining a quantitative quasi-experimental non-equivalent control group design with qualitative action research. The sample consisted of 30 students selected through purposive sampling, divided into an experimental and a control group.The quantitative findings indicated that the use of the Carousel Brainstorming strategy significantly improved students' critical reading comprehension, with a two-tailed significance of p=0.015. The effect size, as measured by Partial Eta Squared, was 0.610, representing a moderate effect (61%). The qualitative results further supported this finding, showing a progressive increase in students' average critical reading comprehension scores from an initial 43.3% to 53.3% after the first cycle and 73.3% after the second cycle.This research demonstrates that the Carousel Brainstorming strategy is an effective and viable method for enhancing students' critical reading skills. The findings have implications for educators, suggesting that this strategy can be incorporated into teaching practices to improve students' critical thinking and reading abilities.